Truth of Floating Carotid Plaques - Wei Liu; Shuo Lu; Yibo Feng; Zhiyong Zhang; Peng Liu; Zunjing Liu (Frontiers in Neurology, 2017)
The floating plaque in carotid artery is an uncommon condition that can be detected by a duplex ultrasonography scan and is a high-risk factor for embolic cerebrovascular disease. The histopathological features of floating plaque in carotid artery vary. To the best of our knowledge, there is still considerable controversy about the treatment of floating carotid plaque. In this case, the floating carotid plaque was located in the edge of atherosclerotic plaque in common carotid artery, pathological finding following carotid endarterectomy confirmed that the mobile substances were formed by the contents of the plaque protruding into the carotid lumen after the rupture of the fibrous cap, without mural thrombus. This pathological change was different from those of the mobile substances, which were commonly considered as mural thrombotic substances of ulcer plaque caused by the ruptures of fibrous cap of vulnerable plaque. According to pathological differences, we investigated pathogenesis of ischemic cerebrovascular disease caused by floating carotid plaque and possible treatments.